2014
DOI: 10.1007/s11948-014-9600-6
|View full text |Cite
|
Sign up to set email alerts
|

Scientists Admitting to Plagiarism: A Meta-analysis of Surveys

Abstract: We conducted a systematic review and meta-analysis of anonymous surveys asking scientists whether they ever committed various forms of plagiarism. From May to December 2011 we searched 35 bibliographic databases, five grey literature databases and hand searched nine journals for potentially relevant studies. We included surveys that asked scientists if, in a given recall period, they had committed or knew of a colleague who committed plagiarism, and from each survey extracted the proportion of those who report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
66
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(71 citation statements)
references
References 59 publications
3
66
0
2
Order By: Relevance
“…На фоне вышесказанного интересны результаты недавнего исследования V. Pupovac и D. Fanelli, кото-рые провели систематический обзор и метаанализ ано-нимных опросов исследователей с целью выяснить, использовали ли они различные формы плагиата в сво-их работах [20]. Выяснилось, что результаты в отно-шении допустимой нормы плагиата были значительно выше ожидаемых.…”
Section: самоплагиатunclassified
“…На фоне вышесказанного интересны результаты недавнего исследования V. Pupovac и D. Fanelli, кото-рые провели систематический обзор и метаанализ ано-нимных опросов исследователей с целью выяснить, использовали ли они различные формы плагиата в сво-их работах [20]. Выяснилось, что результаты в отно-шении допустимой нормы плагиата были значительно выше ожидаемых.…”
Section: самоплагиатunclassified
“…Several authors have attempted to categorize plagiarism into different forms or types [2,7,10,12]. For example, Martin [10] lists several distinct forms of plagiarism: word-for-word plagiarism, paraphrasing plagiarism, plagiarism of secondary sources, plagiarism of the form of a source, plagiarism of ideas and plagiarism of authorship.…”
Section: Types Of Plagiarismmentioning
confidence: 99%
“…Plagiarism 1 and its detection has been a popular area of research for the past 25 years, particularly within academia [1,2,4,12]. Factors, such as the increased availability of freely-accessible digital content, the emergence of online essay banks and writing services, and technological developments are resulting in a rise in plagiarism, particularly in education 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Plagiarism, the misappropriation of other’s intellectual contribution, is a serious form of research misconduct, and probably one of the most frequently reported type of research misconduct (Smith 2000). Despite the challenges in ascertaining the true frequency of plagiarism, recent estimates (around 2 %) suggest that it is much more common than previously thought (Pupovac and Fanelli 2015). However, this high frequency compared to other forms of research misconduct may partially result from enhanced detection by electronic methods.…”
Section: Introductionmentioning
confidence: 97%